„I am not and have never been a communist“: Klaus Mann and his relation to communism - Gołaszewski, Marcin (Acta Universitatis Lodziensis. Folia Germanica, 2023)
Klaus Mann (1906–1949) belonged to generation influenced by the two World Wars, burgeoning communism, and rising nationalism. Political component in his work is very strongly articulated not only in novels and essays, but also in autobiographical work. This emphasises his fascination in times he lived, but most of all it expresses his own involvement in fighting the evil which in his eyes were represented by Hitler and Nazism. In Mann’s eyes communism was not solely represented as a political system, but rather an ally in his personal crusade. In the literature there is often a question asked whether Klaus Mann was a communist or an ideologist whose majority of opinions were in line with ideological assumptions and values of the communist system. Despite clear declarations of the author himself, it is worth to look into his inner development: from fascination through growing distance and eventually disappointment which resulted in detaching himself from the communist ideas.